Investigation of optimal design and operation of a small-scale Low Temperature District Heating (LTDH) with multiple heat sources - Zhao, Weihan (2021)
Improving energy efficiency and reducing carbon emission is among the immediate measures being taken in many countries to address the challenge of climate change. Energy consumption in buildings accounts for over 40% of total primary energy demand in the European Union (EU). Most of this energy is in the form of heat for space heating in buildings which is commonly supplied in building using onsite fossil fuelled-boiler installations in EU. The current fossil fuelled boilers are designed to supply heat at high temperature (about 80 °C) and usually oversized for the required load capacity. This process suffers from low overall thermal efficiency of the heat supply systems. In this project, it was sought to investigate an integrated approach of supplying heat to buildings by aggregating various types of heat sources and delivering heat to a common heat distribution network to form a small-scale district heating system. This is considered as an effective solution to increase efficiency through lowering the hot water temperature and encouraging the adoption of renewable energy systems. Therefore, this thesis investigates the operation and design optimisation of a Low Temperature District Heating (LTDH) network with multiple heat feed-in sources such as a heat pump, biomass boiler, gas boiler and solar thermal collector. A case study to evaluate the design of system was considered as part of the Creative Energy Homes (CEHs) at the University of Nottingham. An overall heat load demand of the site was evaluated using Energy Plus software and a computer model for low temperature heat with multiple heat sources was introduced to optimise different feed-in heat sources. To improve heat provision flexibility, maximise heat generation from renewable sources and provide heat networks flexibility, an optimisation model of the thermal store was also carried out. Furthermore, this work investigated the environmental and economic viability of the proposed low temperature heat network. The case study involves the Creative Energy Homes which consists of seven low energy homes with an aggregate heat load of 44 kW and annual energy consumption of 40258.1 kWh, including 14110.89 kWh for domestic hot water and 26417.92 kWh for space heating. It was established that a system consisting a 1.56 kW solar collector,10 kW heat pump, 15 kW biomass boiler, 20 kW gas boiler and a thermal store of 0.894